2013
DOI: 10.1002/bse.1812
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated Customer Pressures and Environmental Policies in China

Abstract: Drawing on the resource dependence theory, the stakeholder perspective and environmental management capabilities, this study examined the relationship between the heterogeneity of customer pressures and the varying levels of environmental policies in China. Data on 1215 Chinese manufacturing firms were analyzed to demonstrate that environmental pressures emanating from different types of customer have different impacts on firm environmental conduct and that the pressures from multinational consumers have a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…Moreover, our findings add to the current literature on the relationship between stakeholders and firm strategy, which was not well developed in emerging countries (Wu, ). Likewise, although this study was conducted in European countries, the model was not established to inform only about European environmental conditions.…”
Section: Theoretical Framework and Research Hypothesessupporting
confidence: 68%
“…Moreover, our findings add to the current literature on the relationship between stakeholders and firm strategy, which was not well developed in emerging countries (Wu, ). Likewise, although this study was conducted in European countries, the model was not established to inform only about European environmental conditions.…”
Section: Theoretical Framework and Research Hypothesessupporting
confidence: 68%
“…Typically they have access to the decision makers of BFs, and they are mission driven about specific supply regions or sustainability issues. We consider them as direct contributors instead of external stakeholders (Rueda‐Manzanares et al ., ; Wu, ), because they not only create pressure (Foerstl et al ., ) for firms to take actions on supply chain sustainability, but also help BFs to determine which sustainability‐related issues (e.g. carbon, water, child labour etc.)…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Lyon et al () also showed that Chinese firms—even those that had won environmental awards—experienced negative responses to award announcements from shareholders. In China today, the benefit of a superior environmental performance is intangible and limited (Wu, ); winning‐related environmental awards may signal that costly measures have been taken to reduce pollution, resulting in a cost disadvantage over competitors (Lyon et al, ). If corporate EID that has been released is deemed relevant, it would be integrated into investors' and financial analysts' evaluations of corporate value or future profitability (Cormier & Magnan, ; Gallego‐Alvarez et al, ).…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%